Ainex 2019- UMP’s search talent platform for students to invent or innovate cost-effective and eco-friendly products - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP)’s Advanced Innovation and Engineering Exhibition 2019 (AiNEX 2019) received 50 entries of research products created by secondary and university students with this year’s theme focusing on products that were cost-effective and environmental-friendly.